Regulation of the MEK/ERK signaling cascade by ADAM12 in triple-negative breast cancer cells - Hodge, Jacob G. (Kansas State University, 2016)
Mitogen-activated protein kinase (MAPK) signaling plays an important role in the proliferation, survival, and therapy resistance of breast cancer cells. Two important protein kinases involved in the MAPK pathway are MEK and ERK. The MEK/ERK signaling cascade can be stimulated by activation of the epidermal growth factor receptor (EGFR) upon binding of EGF-like ligands, which are released from cells by ADAM proteases. EGFR is frequently overexpressed in triple-negative breast cancer (TNBC), a particularly aggressive form of breast cancer. Our analysis of clinical data revealed that high expression of ADAM12, but not other ADAMs, in TNBC is associated with poor patient survival. Thus, we hypothesized that ADAM12 plays a critical role in the progression of TNBC, possibly by stimulating MEK/ERK activity in an EGFR-dependent manner. To test this hypothesis, ADAM12 was knocked-down (KD) in SUM159PT TNBC cells, which express high levels of the endogenous ADAM12 protein. An antibody array assay indicated a significant decrease in the activation of the MAPK pathway in SUM159PT cells after ADAM12 KD. The decrease in MAPK activity was further confirmed by Western blotting using phospho-MEK and phospho-ERK specific antibodies. Additionally, conditioned media from ADAM12-deficient SUM159PT cells failed to support the survival of MCF10A cells, suggesting that ADAM12 KD reduced the release of pro-survival growth factors from SUM159PT cells. Based upon this data, we propose that ADAM12 is a novel regulator of the MAPK pathway and a potential therapeutic target in breast cancer.
Keywords: Breast cancer; Cell signaling; Protein chemistry; Stem cells; Genetic mutations; Membrane receptors